IDENTIFIKASI SENYAWA ANTIMIKROBA ALAMI PANGAN PADA EKSTRAK KULIT BUAH NAGA MERAH DENGAN MENGGUNAKAN GC-MS [Identification of Food Natural Antimicrobe Compound from Red Dragon Fruit Peel Extract by GC-MS] - Dewi Sartika; Sutikno Sutikno; Neti Yuliana; Syarifah R M (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2019)
The peel of red dragon fruit have a natural antimicrobe potency. This research have aim to explore the peel of red dragon fruit as an antimicrobe with used GC-MS. The result of research showed that content of the peel of red dragon fruit was dominated by ascorbic acid 2,6-dihexadecanoate (26,56%), oleic acid (24,08%), estra-1,3,4(10) trien-17 beta-ol (9,63%), 9,12-octa deca dienoic acid (Z,Z) (8,27%), and organic acid compound, phenol, flavonoid, esther (31,46%) that had an antimicrobe potency. The aplication of the red dragon fruit peel on Tongkol fish that was contaminated with E coli, showed that, there is a decrease of E coli as much as 1.47 x 109 koloni/g, significantly. The conclusion of research was the peel of red dragon fruit have a natural antimicrobe potency.